2018
DOI: 10.1177/0033354918798809
|View full text |Cite
|
Sign up to set email alerts
|

Building Healthy Community Environments: A Public Health Approach

Abstract: Environmental quality has a profound effect on health and the burden of disease. In the United States, the environmentrelated burden of disease is increasingly dominated by chronic diseases. At the local level, public health practitioners realize that many policy decisions affecting environmental quality and health transcend the authorities of traditional health department programs. Healthy decisions about the built environment, including housing, transportation, and energy, require broad collaborative efforts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 39 publications
(38 reference statements)
0
24
0
3
Order By: Relevance
“…The goals of sustainable community development are to increase land production by maximizing resource utilization, to promote resource recycling by utilizing waste, to promote a sustainable lifestyle by changing the community environment to relax the residents' spirit and stabilize their emotions, to improve communication by encouraging every member to participate in community building, and to foster community attachment by holding interactive activities. As western experts and scholars have done in recent years, one of the sustainable development paths of old communities is to improve health and enhance well-being [31,32], which is in line with the goals of community sustainable development ( Figure 1). The definition of health was set out by WHO (1946) as follows: 'Health is not merely the absence of disease and infirmity but a state of optimal physical, mental and social well-being' [33,34].…”
Section: Introductionmentioning
confidence: 75%
“…The goals of sustainable community development are to increase land production by maximizing resource utilization, to promote resource recycling by utilizing waste, to promote a sustainable lifestyle by changing the community environment to relax the residents' spirit and stabilize their emotions, to improve communication by encouraging every member to participate in community building, and to foster community attachment by holding interactive activities. As western experts and scholars have done in recent years, one of the sustainable development paths of old communities is to improve health and enhance well-being [31,32], which is in line with the goals of community sustainable development ( Figure 1). The definition of health was set out by WHO (1946) as follows: 'Health is not merely the absence of disease and infirmity but a state of optimal physical, mental and social well-being' [33,34].…”
Section: Introductionmentioning
confidence: 75%
“…Based on empirical data, Wells and Evans explained the relationship between public health and the ecological living environment of citizens [ 22 ]. Given the existing research results, Koehler et al proposed a conceptual framework to consider the impact of environmental decision-making on public health, further emphasizing that public health is not only related to the living environment but also to local transportation and energy [ 23 ]. Various resources in the ecological environment are closely related to the survival of human beings, and they also have a significant impact on the public health level.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported that 23% of deaths between 2006 and 2016 were attributable to environmental causes 4 5. Environmental health once focused on the prevention of infectious diseases; however, the focus has shifted toward chronic diseases such as cardiovascular diseases 6. The WHO estimated that ischaemic heart disease is the biggest killer worldwide (16% of total deaths) in 2019 7.…”
Section: Introductionmentioning
confidence: 99%